PENGARUH KECUKUPAN MODAL, LIKUIDITAS, KUALITAS KREDIT DAN BOPO TERHADAP PROFITABILITAS PERUSAHAAN PERBANKAN PADA BURSA EFEK INDONESIA - Mohammad Anis Fahruddin, 11.4202.0056 (Students Journal of Economic and Management, 2013)
This study aimed to examine the effect of Capital Adequacy Ratio, Liquidity, Credit Quality, the Operational Cost to Operational Expenses (BOPO) of the banks profitability. The study population consisted of 30 banks to go public. Sample was determined by purposive sampling technique. The data in this study using the merger or the pooling of data is from the year 2009 to the year 2011 the company sample. The results of this study include: (1). The capital adequacy ratio and no significant negative effect on the profitability of the bank. (2). Liquidity has positive and significant impact on the profitability of the bank. (3). Credit quality and significant negative effect on the profitability of the bank. (4). the Operational Cost to Operational Expenses (BOPO) and significant negative effect on the profitability of the bank. Keywords: Capital Adequacy Ratio, Liquidity, Credit Quality, the Operational Cost to Operational Expenses (BOPO) and profitability